Enantiospecific Reassessment of the Pharmacokinetics and Pharmacodynamics of Oral Eflornithine against Late-Stage Trypanosoma brucei gambiense Sleeping Sickness - Jansson-Löfmark, R. (Antimicrob Agents Chemother, 2015)
This study aimed to characterize the stereoselective pharmacokinetics of oral eflornithine in 25 patients with late-stage Trypanosoma brucei gambiense sleeping sickness. A secondary aim was to determine the concentrations of l- and d-eflornithine required in plasma or cerebrospinal fluid (CSF) for an efficient eradication of the T. brucei gambiense parasites. Patients were randomly allocated to receive either 100 (group I, n = 12) or 125 (group II, n = 13) mg/kg of body weight of drug every 6 h for 14 days. The concentrations of l- and d-eflornithine in the plasma and CSF samples were measured using a stereospecific liquid chromatographic method. Nonlinear mixed-effects modeling was used to characterize the plasma pharmacokinetics. The plasma concentrations of l-eflornithine were on average 52% (95% confidence interval [CI], 51, 54%; n = 321) of the d-enantiomer concentrations. The typical oral clearances of l- and d-eflornithine were 17.4 (95% CI, 15.5, 19.3) and 8.23 (95% CI, 7.36, 9.10) liters/h, respectively. These differences were likely due to stereoselective intestinal absorption. The distributions of eflornithine enantiomers to the CSF were not stereoselective. A correlation was found between the probability of cure and plasma drug exposure, although it was not more pronounced for the l-enantiomer than for that of total eflornithine. This study may explain why oral treatment for late-stage human African trypanosomiasis (HAT) patients with racemic eflornithine has previously failed; the more potent l-enantiomer is present at much lower concentrations in both plasma and CSF than those of the d-enantiomer. Eflornithine stereoselective pharmacokinetics needs to be considered if an oral dosage regimen is to be explored further.